2013
DOI: 10.4155/fmc.13.174
|View full text |Cite
|
Sign up to set email alerts
|

Arylsulfone-Based HIV-1 Non-Nucleoside Reverse Transcriptase Inhibitors

Abstract: HIV-1 non-nucleoside reverse transcriptase inhibitors (NNRTIs) represent one of the most significant classes of drugs for the treatment of AIDS/HIV infection. Over the past two decades several potent arylsulfone-based HIV-1 NNRTIs and related analogs have been developed. This review provides an essential overview of the structure-activity relationships of the arylsulfone-based HIV-1 NNRTIs. Furthermore, structural information useful for the design and development of new sulfur containing NNRTIs with enhanced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…The same trend was observed when the substitution occurred at the 6-position of the phenyl ring (entries [13][14][15][16][17]. Exhilaratingly, the compounds with an electron-donating group on the same position provided superior inhibitory activity to the corresponding indolealkyl trifluoropyruvate derivatives (entries [10][11][12]. Other important SAR information is as follows: (1) installation of the ethyl group at R 3 induced more robust inhibition than their methyl analogues (entries 1 vs. 28, 3 vs. having a substituent group at the 4-position or the 2-position resulted in an overall decrease in potency (entries 9 vs. 19, 10 vs. 21, 12 vs. 20); (4) N-protected indoles also gave moderate but reduced anti-HIV-1 activities which demonstrated the significance of NH in heterocycles for blocking the reverse transcriptase (entries 24, 25 and 26); (5) the cytotoxicity (CC 50 values) study showed that indole-based α-amino acids 19 and 29 had good SI values of >1825.8 and 1095.4, respectively (entries 5 and 15).…”
Section: Structure-activity Relationship (Sar) Studiessupporting
confidence: 69%
See 1 more Smart Citation
“…The same trend was observed when the substitution occurred at the 6-position of the phenyl ring (entries [13][14][15][16][17]. Exhilaratingly, the compounds with an electron-donating group on the same position provided superior inhibitory activity to the corresponding indolealkyl trifluoropyruvate derivatives (entries [10][11][12]. Other important SAR information is as follows: (1) installation of the ethyl group at R 3 induced more robust inhibition than their methyl analogues (entries 1 vs. 28, 3 vs. having a substituent group at the 4-position or the 2-position resulted in an overall decrease in potency (entries 9 vs. 19, 10 vs. 21, 12 vs. 20); (4) N-protected indoles also gave moderate but reduced anti-HIV-1 activities which demonstrated the significance of NH in heterocycles for blocking the reverse transcriptase (entries 24, 25 and 26); (5) the cytotoxicity (CC 50 values) study showed that indole-based α-amino acids 19 and 29 had good SI values of >1825.8 and 1095.4, respectively (entries 5 and 15).…”
Section: Structure-activity Relationship (Sar) Studiessupporting
confidence: 69%
“…21 At the same time, non-racemic trifluoromethylated indoles (TFMIs) represent another type of indole-based derivative; however, there has been limited information regarding the enantioselective discrimination of reverse transcriptase (RT) of HIV-1 with these non-racemic indole derivatives. In 2013, our group developed enantioselective and efficient inhibitors of reverse transcriptase (RT) of HIV-1 based on TFMIs by a TZMbl cell assay (11,Scheme 2). 22,23 The inhibitory activity of the two enantiomers and racemic ones was compared.…”
mentioning
confidence: 99%
“…The U-5C-4CR can be extremely powerful in getting access to molecular diversity and complexity when the linear adduct is further manipulated in a post-MCR transformation. Chiral highly functionalized dihydroisoquinolines and isoindoles were synthesized by Dyker and coworkers using U-5C-4CR followed by a gold-catalyzed hydroamination [31,32]. Dyker et al used L-valine as the chiral amine component, and benzaldehydes with an alkyne moiety to generate highly functionalized secondary amines converted in dihydroisoquinolines 111 and 112 by a 6-endo-dig cyclization (23% and 35% yield) or in isoindoles 110 by a 5-exo-dig cyclization and subsequent aromatization such as in 113 and 114 (38% and 49%, Scheme 24).…”
Section: Scheme 22mentioning
confidence: 99%
“…Since diaryl sulfone and N-phenylbenzenesulfonamide derivatives have been synthesized in this work, in this section, we will point out the importance of these compounds as well as a brief discussion covering other synthetic strategies for the synthesis of these compounds. Diaryl sulfones are useful intermediates due to their interesting biological [13][14][15][16][17] and chemical [18][19][20] properties. Diaryl sulfone derivatives are either an antibiotic like dapsone for the treatment of leprosy 13 or have anti-HIV-1 activity like 2-nitrophenyl phenyl sulfone, 14 N-(5-bromo-3-((4-chlorophenyl)sulfonyl)thiophen-2-yl) acetamide, 15 2-amino-6-arylsulfonylbenzonitrile, 16 pyrrylarylsulfone 17 and indolylaryl sulfones 14 (Fig.…”
Section: Introductionmentioning
confidence: 99%